Friends of Dementia - Cheong, Hazel Kai Qi (2017)
This paper presents Friends of Dementia, a campaign to promote the creation of a dementia-friendly community in Singapore, initiated by three final year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University (NTU). The campaign aimed to educate and empower Institute of Higher Learning (IHL) students from universities and polytechnics on the issue of dementia, hence becoming a Friend of Dementia who contributes positively towards building a dementia-friendly community. The paper outlines the primary and secondary research which helped to guide the campaign’s message and strategies. Apart from delving into current literature, a survey and focus group discussions were conducted to gain a deeper understanding of IHL students’ knowledge, attitude and behaviour towards dementia, people with dementia and a dementia-friendly community. The insights from the formative research helped to inform the campaign’s strategy which aimed to educate IHL students to become a Friend of Dementia, as well as to affect attitudinal and behavioural changes. Online platforms were also extensively used to extend the campaign’s reach. Offline platforms were used to directly engage IHL students and enhance the persuasiveness of our key messages in order to effect the desired change in our target audience. The paper concludes with an evaluation of the campaign’s objectives, key messages and strategies via a thorough analysis of the post-campaign survey, media coverage and appraisals. The paper also discusses the sustenance of the campaign through collaboration with key partners. Finally, the appendices contain the campaign’s collaterals and lists which detail its execution.